Knowledge of Hazards Associated With Urban Livestock Farming in Southeast Nigeria - Asadu, Anthonia N.; Chah, Jane M.; Attamah, Clement O.; Igbokwe, Edwin M. (Frontiers in Veterinary Science, 2021)
The study assessed urban farmers' knowledge of health hazards associated with Urban Livestock Farming (ULF) in Southeast Nigeria. Multistage and random sampling techniques were used to select 210 respondents. Structured interview schedule was used to collect data. Data collected were analyzed using descriptive and inferential statistics. Major type of animals reared was broiler. A good proportion of the respondents had a high knowledge of hazards associated with livestock keeping. However, some farmers did not know that animal products from intensive system can be contaminated with heavy metals and that animal dung should be treated before use for crop cultivation. There was a significant influence of socio-economic characteristics of farmers on knowledge of hazards posed by livestock keeping. Farmers' knowledge of hazards varied significantly between the three states studied. Farmers therefore need technical advice to fully understand the hazards associated with urban livestock farming and their consequences as well as on pre-treatment of dung to reduce transfer of pathogens.